Cultural Hegemony in Aravind Adiga’s The White Tiger - Shivani Mishra; Ritu Pandey (LET: Linguistics, Literature and English Teaching Journal)
This paper explores the role of cultural hegemony in perpetuating caste- and class-based oppression in contemporary India through a critical reading of Aravind Adiga’s The White Tiger. Grounded in Antonio Gramsci’s theory of hegemony, it examines how ideological consent, coercion, and institutional complicity normalize systemic domination. The novel portrays how caste and class hierarchies persist not just through overt force, but through cultural mechanisms that internalize obedience among the oppressed. Balram Halwai’s morally ambiguous rise from rural servitude to urban entrepreneurship reflects a critique of the entrenched structures of power that manipulate ideology, economy, and identity. Through qualitative textual analysis, the paper reveals how moments of rebellion, while disruptive, and are often reabsorbed into hegemonic systems. Ultimately, the study emphasizes literature’s capacity to critique and challenge dominant ideologies, situating The White Tiger within broader debates on power, resistance, and subaltern agency in Indian fiction and cultural discourse.